The clinical and molecular epidemiology of Streptococcus agalactiae in Kenya: maternal colonisation and perinatal outcomes - Seale, A; Anna C Seale (2015)
Two cellular processes of central importance to cancer and neurodegeneration are apoptosis and cellular senescence. Both are a means of cellular suicide that are utilized in time- and context-dependent manners and have important evolutionary purposes. However, they are also the drivers of many deleterious processes underlying cancer and neurodegeneration. Many of the cellular responses to aging and age-related diseases, including apoptosis and senescence, converge on the tumor suppressor pathway, p53. Here I examine the molecular basis for loss of cell polarity and accelerated cell death mediated by apoptosis stimulating protein of p53 2 (ASPP2) in neurodegeneration. In this study we find that ASPP2 mediates STAT1Linduced apoptosis. Lipopolysaccharide (LPS) induces ASPP2 mRNA expression in vitro. Also, LPS induces nuclear ASPP2 in vivo at the blood-cerebral spinal fluid-barrier (BCSFB), the brain's barrier to inflammation. Consistent with ASPP2's role as a gatekeeper to inflammation, ASPP2 mutant mouse brains possess enhanced neuroinflammation. Elevated ASPP2 expression is also observed in mouse models and human neuroinflammatory disease tissue in astrocytes. The identification of ASPP2 as a novel transcriptional target of STAT1 and the observed increase in ASPP2 expression in both mouse and human neuroinflammatory disorders, suggests that the identified STAT1/ASPP2 pathway may connect tumor suppression and cell polarity to neuroinflammation. Additionally, I investigate the regulation of cellular senescence by p53 isoforms as a means to enhance neuroprotection of astrocytes in chronic neurodegenerative diseases, Alzheimer's disease (AD) and amyotrophic lateral sclerosis (ALS). Here we report that p53 isoforms, Δ133p53 and p53β, are endogenous regulators of cellular senescence in the central nervous system (CNS). Δ133p53 functions as a dominant-negative regulator of full-length (FL)Lp53 and represses senescence, while p53β as a co-activator of FLLp53, promotes senescence. In neurodegenerative disease brain tissue, FLL53 and p53β are upregulated while Δ133p53 is downregulated. We demonstrate that Δ133p53 and p53β directly regulate astrocyte senescence, including the release of key neurotoxic proL inflammatory cytokines such as ILL6 and ILL1β. Also, we show that the p53 isoform switch that occurs during aging and neurodegeneration promotes neuronal toxicity using coL culture experiments with human iPSC-derived motor neurons and human astrocytes. We also demonstrate that astrocyte senescence can be rescued through overexpression of Δ133p53, revealing a promising therapeutic approach to delay or inhibit the progression of neurodegeneration.